The effect of morphotropic phase boundary on dielectric properties of Bi 0.5Na 0.5Ti 1-x Zr x O 3 solid solutions - Rachakom A. (2014)
Lead-free bismuth sodium titanate zirconate (Bi 0.5Na 0.5Ti 1-x Zr x O 3 or BNTZ) solid solutions with varied composition of x=0.50, 0.55, 0.58, 0.60, 0.63, 0.65, 0.68, 0.70, 0.73, 0.75 and 0.78 mol fraction were obtained using a conventional mixed-oxide method. XRD analysis indicated that the increase in concentration of Zr led to compositions across morphotropic phase boundary region. A quantitative structural investigation was carried out using the X-ray powder diffraction data. The rhombohedral phase was found to dominate for x<0.68 with space group R3c. In the morphotropic phase boundary (MPB) region i.e. 0.68≤x≤0.75, it was demonstrated that coexistence of rhombohedral and orthorhombic phase was observed. For x=0.78, the phase was completely orthorhombic with space group Pmna. Furthermore, the dielectric properties showed some enhanced activity of dipole movement at MPB boundaries which supported the presence of MPB region in this material system. © 2012 Elsevier Ltd and Techna Group S.r.l.